2017
DOI: 10.1007/s40167-017-0052-0
|View full text |Cite
|
Sign up to set email alerts
|

Culture and emotion perception: comparing Canadian and Japanese children’s and parents’ context sensitivity

Abstract: Prior research on the perception of facial expressions suggests that East Asians are more likely than North Americans to incorporate the expressions of background figures into their judgment of a central figure’s emotion (Masuda et al. in J Pers Soc Psychol 94:365–381, 2008b). However, little research has examined this issue in the context of developmental science, especially during joint sessions where parents engage in a task in front of their 7–8-year-old children. In this study, 22 Canadian and 20 Japanese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Under the rubrics of scaffolding processes (Wood et al, 1976), guided participation (Rogoff, 2003), zone of proximal development (Cole, 1996;Greenfield & Bruner, 1969;Luria, 1976;Vygotsky, 1930Vygotsky, /1978, joint attention (Tomasello, 1999), and cultural transmission (Mesoudi, 2011;Richerson & Boyd, 2005), cultural psychologists have also examined how parental guidance directly influences children's patterns of attention during tasks (Fernald & Morikawa, 1993;Ishii, Miyamoto, Rule, & Toriyama, 2014;Lee et al, 2017;Senzaki et al, 2016). These studies demonstrated that caregivers directed their children's attention in culturally dominant ways: North American mothers tended to direct infants to attend to focal objects, whereas Japanese mothers tended to direct infants to attend to the MASUDA 9 of 16 relationships between focal and background objects.…”
Section: Research On Cultural Transmission Processesmentioning
confidence: 99%
“…Under the rubrics of scaffolding processes (Wood et al, 1976), guided participation (Rogoff, 2003), zone of proximal development (Cole, 1996;Greenfield & Bruner, 1969;Luria, 1976;Vygotsky, 1930Vygotsky, /1978, joint attention (Tomasello, 1999), and cultural transmission (Mesoudi, 2011;Richerson & Boyd, 2005), cultural psychologists have also examined how parental guidance directly influences children's patterns of attention during tasks (Fernald & Morikawa, 1993;Ishii, Miyamoto, Rule, & Toriyama, 2014;Lee et al, 2017;Senzaki et al, 2016). These studies demonstrated that caregivers directed their children's attention in culturally dominant ways: North American mothers tended to direct infants to attend to focal objects, whereas Japanese mothers tended to direct infants to attend to the MASUDA 9 of 16 relationships between focal and background objects.…”
Section: Research On Cultural Transmission Processesmentioning
confidence: 99%
“…We wanted to see each mother's tendency to use social evaluative expressions constantly while watching others’ social behaviors with infants. Therefore, following previous studies that compared maternal speech between Japanese and Canadians using similar types of materials (i.e., short presentations of social stimuli; Lee, Nand, et al., ; Masuda et al., in press), we used the current coding scheme.…”
mentioning
confidence: 99%
“…However, when working on a task with their parents, older children (ages 7 to 9 years) do demonstrate culturally specific attentional styles (i.e., local attention in Western/global attention in Eastern). Thus, it is possible that children gradually develop a dominant attentional style based on their daily parental interactions (Lee et al, 2017). In the current context, we hypothesize that these differences in attentional styles influence variation in the ability to integrate local features (recognizing elements of an object's features; car doors) and global features (recognizing the configuration of the entire object; size and shape) in object processing.…”
Section: Relationship Between Children's Scale Errors and Categorization Abilitymentioning
confidence: 93%